Odpowiedzi

2010-03-02T13:45:42+01:00
[(x²+2)-(-x²+x+1)]*2x-1 =
[x²+2+x²-x-1]*2x-1 =
(2x²-x+1)*2x-1 =
4x³-2x²+2x-1
  • Roma
  • Community Manager
2010-03-02T13:50:46+01:00
[(x² + 2) - (- x² + x + 1)]*2x - 1 = (x² + 2 + x² - x - 1)*2x - 1 = 2x³ + 4x + 2x³ - 2x² - 2x - 1 = 4x³ - 2x² + 2x - 1

Spr.
x = 0
[(x² + 2) - (- x² + x + 1)]*2x - 1 dla x = 0
= [(0² + 2) - (- 0² + 0 + 1)]*2*0 - 1 = (2 - 1)* 0 - 1 = 0 - 1 = - 1
4x³ - 2x² + 2x - 1 dla x = 0
= 4*0³ - 2*0² + 2*0 - 1 = 0 - 0 + 0 - 1 = - 1

x = 1
[(x² + 2) - (- x² + x + 1)]*2x - 1 dla x = 1
[(1² + 2) - (- 1² + 1 + 1)]*2*1 - 1 = [(1 + 2) - (-1 + 1 + 1)]*2 - 1 = (3 - 1)*2 - 1 = 4 - 1 = 3
4x³ - 2x² + 2x - 1 dla x = 1
= 4*1³ - 2*1² + 2*1 - 1 = 4*1 - 2*1 + 2 - 1 = 4 - 2 + 2 - 1 = 3